Ideal MHD Ballooning Stability in the Vicinity of a Separatrix - Bishop, Christopher; Kirby, P.; Connor, J. W.; Hastie, R. J.; Taylor, J. B. (Nuclear Fusion, 1984)
Using a model tokamak equilibrium, the influence of a magnetic separatrix on the stability of the plasma against ideal MHD ballooning modes is investigated. It is found that there is no significant stabilizing effect from the strong global shear near the separatrix, but rather that marginal stability is controlled mainly by the poloidal position of the X-point. A physical interpretation of these results is given.